SIKAP TOKOH PEREMPUAN SASTRA JAWA MODERN DALAM MENGHADAPI KEKERASAN[1] Â» Darni Kekerasan terhadap Perempuan dalam Fiksi Jawa ModernDarni (Lentera, Jurnal Studi Perempuan, 2010)
Abstract The re is 3 position posed at by ihe w oma n fignres in facing hardness befalling the r x ’self Most ofthem acts surrenderness. They donthave ihe pemer or unables to do something. They only can surrender gazes at its (the bad chance. They nordoes something because don t diseuss i t isfurther about aetion offigura. Even some of something experiences hardness until dying, s o i ha t unknown position hereinafter. But a/so there is rise makes against variously. There is also tries getting out of hardness then self-snpporting. Mosi of f hem is neglected vietim. Third the thing will be diseussed in detail at solution following. Kata Kunci: sureenderness, fights against,self-snpporting                                           ^